Percutaneous Needle Electrolysis Reverses Neurographic Signs of Nerve Entrapment by Induced Fibrosis in Mice - Margalef, R. (Evid Based Complement Alternat Med, 2020)
Nerve entrapments such as carpal tunnel syndrome are the most common mononeuropathies. The lesional mechanism includes a scarring reaction that causes a vascular compromise. The most effective treatment is surgery, which consists of removing the scarred area, thus reverting the vascular impairment. In the present study, a more conservative therapeutic approach has been undertaken to release the nerve by means of galvanic current (GC) applied with a needle: percutaneous needle electrolysis (PNE). For this purpose, a mouse model of sciatic nerve entrapment has been created using albumin coagulated by glutaraldehyde (albumin 35% and glutaraldehyde 2% volume applied, 10 μl). After two weeks, a fibrous reaction was obtained which entrapped the nerve to the extent of causing atrophy of the leg musculature (14.7%, P < 0.05 compared to the control leg). Ultrasound imaging confirmed that the model's image was compatible with that of nerve entrapment in patients. To quantify the degree of entrapment, nerve conduction recordings were made. The amplitude (peak-to-peak) of the compound muscle action potential (CMAPs) decreased by 32.2% (P < 0.05), and the proximal latency increases by 17.7% (P < 0.05, in both cases). In order to release the sciatic nerve, PNE was applied (1.5 mA for 3 seconds and 3 repetitions; 1.5/3/3) by means of a solid needle in the immediacy of perineural fibrosis before and 5 minutes after the application of GC, and the proximal latency shows a decrease of 16% (P < 0.05). The recovery of CMAPs amplitude was about 48.7% (P < 0.05). Three weeks later, the CMAPs amplitude was almost completely recovered (94.64%). Therefore, with the application of GC by means of a solid needle, the sciatic nerve was definitively released from its fibrous entrapment.